Language acquisition in Croatian 5- to 7-year-old children: Where have gender differences gone? - Mildner, Vesna; Bajzec, Martina (2012)
There is evidence that at early chronological age girls and boys differ, among other characteristics, with respect to speech and language acquisition and use. The aim of this study was to test whether these gender differences recorded at early verbal age persist until school age. The study was conducted on a sample of healthy 58 children (28 girls and 30 boys), aged five to seven years, native speakers of Croatian. Each child completed two tasks: (1) telling a story from a series of cartoons, and (2) free conversation with the experimenter. We measured three parameters: (a) total amount of speech produced by the child ; (b) proportion of various categories of words ; and (c) vocabulary size. Our results indicate that any gender differences present at early stages of speech and language acquisition are equaled out by the time the children start elementary school.
ENG